1988
DOI: 10.1136/oem.45.7.469
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and response to methyl isocyanate: results of a community based survey in Bhopal.

Abstract: In the two weeks immediately after the Bhopal disaster a community based survey was carried out in a series of eight exposed and two non-exposed clusters of households. The primary concern was the effect of the gas (subsequently identified as methyl isocyanate) on the eyes of the victims but data were also sought on respiratory status and the first symptoms of the exposure. No case of blindness was encountered that could be attributed to the gas. The most frequent symptoms reported were burning of the eyes, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…During the first two months after the exposure, victims reported severe ocular burning, watering, pain and photophobia [22]. These findings are similar to the findings of ICMR clinical studies compiled in its recent report [2].…”
Section: Ocular Health Effectssupporting
confidence: 81%
See 1 more Smart Citation
“…During the first two months after the exposure, victims reported severe ocular burning, watering, pain and photophobia [22]. These findings are similar to the findings of ICMR clinical studies compiled in its recent report [2].…”
Section: Ocular Health Effectssupporting
confidence: 81%
“…According to the ICMR, neuromuscular defects, such as tingling numbness, sensation of pins and needles in the extremities, and muscle aches, have continued among the victims after exposure [24]. Such effects of MIC exposure could be attributed to the prevention of formation of muscle fibres in the culture at low doses and causing death of fibroblasts and myoblasts at higher doses [22]. It was observed that out of 208 persons suffering from psychological problems, 45% suffered from neuroses, 35% from anxiety states and 9% from exacerbation of preexisting adjustment reactions [25].…”
Section: Psychological and Neurological Health Effectsmentioning
confidence: 99%
“…Findings from early ocular studies conducted 8-60 days after exposure to MIC revealed predominantly injuries resulting from the intensely irritating effect of MIC on the cornea causing severe ocular burning, watering, pain, and photophobia [9]. Follow-up ocular studies, conducted 9 months [10] to 2 yr [11] after exposure, reported chronic irritant symptoms such as persistent eye watering, burning, itching, and redness.…”
Section: Discussionmentioning
confidence: 99%
“…Within a few days after the accident, Andersson et al (12) carried out a survey of acute effects on eight exposed and two nonexposed household clusters in Bhopal. Exposure zones were marked out based on reports of human and animal deaths and on symptoms and perceptions of the presence of the gas.…”
Section: Existing Health Studiesmentioning
confidence: 99%
“…In a community-based exposure and response study, Andersson et al (12) reported duration of exposure for 379 subjects. About 57% were exposed for 1-3 hr, and 29% reported staying in the exposed area throughout the estimated exposure period of 4 hr.…”
Section: Symptommentioning
confidence: 99%